PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP UNDERPRICING SAHAM DI PERUSAHAAN YANG MELAKUKAN IPO DI BEI TAHUN 2020-2021 - Lia Amalia Kartika; Yogi Ginanjar; Eva Fauziah Ahmad (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Underpricing is a phenomenon where the stock price in the primary market is lower than the stock price when traded in the secondary market. Many companies set their prices too low and sufferunderpricing so that the funding obtained from the IPO is not optimal. This study aims to determine the effectprofitability, leverage,company size and company ageunderpricing shares. The population of this study are companies that are conducting an IPO on the IDX in 2020-2021. Selection of samples using techniquespurposive sampling, the samples obtained amounted to 86 companies. The data collection method used is data documentation. The data analysis technique used in this study is multiple linear regression analysis. The research results show thatprofitabilityand company size partially has no significant effect onunderpricing share. Whereas,leverage and company age partially have a significant effect onunderpricing shares